Pengembangan Usaha Produksi Celana Anak UMKM Konveksi EV_Kids Product Desa Ambokulon, Kecamatan Comal, Kabupaten Pemalang - Siti Masrokhah; Tri Handayani; Rengga Kusuma Putra; Nunung Wulan Sari; Anini Nihayah; Arif Hadi Prasetyo; Akhmad Maulana Malik; Sandya Khaela Nurisma; Diana Puspitasari; Fitriana Putri Kurniawati (Lembaga Pengembangan Kinerja Dosen, 2025)
In Indonesia, micro, small, and medium enterprises (MSMEs) have long been recognized as a very important business sector due to their various real roles in the economy. However, MSMEs often face many obstacles in running their businesses. More incentive support from various parties, especially the government, is needed for the development of MSMEs. In order to overcome the problems faced by MSMEs and support their sustainability, a KKU (Business Field Study) activity was carried out by Group 15 at the KKU-11 of the Institute of Technology and Business (ITB) Adias Pemalang at the MSME “Ev_Kids Product.”After conducting an observation phase, several problems faced by the SME were identified, including the lack of social media for marketing, failure to calculate the Cost of Goods Sold (COGS) and maintain simple accounting records, absence of a business logo, banners, promotional image designs, organizational structure, business profile, product catalog, stamps, receipt books, and product attributes. Additionally, the SME had never produced a production video or promotional video.After conducting the observation phase, KKU actors formulated several business development assistance programs, namely creating social media accounts, calculating the Cost of Goods Sold (COGS), creating simple bookkeeping, creating a business logo, banners, promotional image designs, organizational structure, business profile, product catalog, stamps, note books, and product attributes in the form of hangtags. They also created production videos and promotional videos.